Alâ€‘‘aqd Alâ€‘sahih: The Legal Basis for Determining the Validity of Islamic Financial Transactions - Ishola, Abdullahi Saliu; Azeez, Yusuf Abdul; Ali, Norfadhilah Mohamad (International Journal of Economics and Financial Issues, 2016)
There is no modern activity premised on Islamic Law that does not have a link with one of the traditional practices in the classical Islamic Law society. Failure to find its root in the past may even be a justification for such activity to be rejected as alien to Islamic Law. The contemporary Islamic Financial Transactions (IFT) otherwise referred to as Islamic Banking System (IBS), cannot equally be free from that inevitable litmus test. Consequently, through the principles of al-‘aqd al-sahih (a valid contract) in Islamic Law, the inexplicable requirements for the activities of the Islamic Banking and Finance (IBF) to be Shari‘ah compliant could be more easily and reasonably spelt out while the extent of such a compliance could be clearly assessed. This paper, therefore, examines the role of al-‘aqd al-sahih as the pivotal instrument for validating any IFT and its obligations. Thus, what will make any contract to be invalid in Islamic law is primarily applicable to any IBF transactions in the modern world. The study emphasises the danger in losing the sight of the contractual nature/basis of IBF Transactions and hypothesis that al-‘aqd al-sahih is the pivotal legal basis for the validity of IFT. Keywords: Islamic Financial Transactions (IFT), Islamic Banking and Finance (IBF), al-‘aqd al-sahih, Shari‘ah compliant, Islamic Law JEL Classification: G2